18F-FDOPA and MRI Findings in a Case of Multiple Sclerosis. (26th November 2022) - Lersy, François; Kremer, Stéphane; Chibbaro, Salvatore; Namer, Izzie Jacques; Bund, Caroline
Abstract: A 39-year-old woman with no significant medical history underwent a brain MRI because of headaches and dysarthria having lasted 3 weeks. A tumor lesion was suspected. PET imaging was decided. She underwent FDG and FDOPA PET, leading to the diagnosis of low-grade glioma. Three months later, a new imaging assessment was organized. It showed a decrease in the hypermetabolism of the lesion and the appearance of a second lesion questioning the diagnosis. Further assessment led to the conclusion of a multiple sclerosis. This case illustrates that FDOPA PET uptake should be interpreted with caution in patients with suspected primary brain tumors.